Return of Sexual Activity Within Six Weeks of Childbirth Among Married Women Attending Postpartum Clinic of a Teaching Hospital in Ethiopia - Edosa Dirirsa, Dejene; Awol Salo, Mukemil; Eticha, Tariku Regea; Geleta, Tinsae Abeya; Deriba, Berhanu Senbeta (Frontiers in Medicine, 2022)
Introduction: Postpartum sexual health gets very little attention compared to pregnancy and childbirth, even though most maternal deaths and disabilities occur during this time. Therefore, the study aimed to assess return of sexual activity within six weeks of childbirth among married women attending postpartum clinic of a teaching hospital in Ethiopia, 2021. Methods: The hospital-based cross-sectional study design was implemented from September to October 2021. Eligible postpartum women were sampled by systematic random sampling technique. The data was entered into EPI-info and exported to SPSS version 24 for further analysis. All variables with a p-value < 0.05 in multivariable analyses were taken as associated factors with the return to sexual activity before six weeks of childbirth. Results: A total of 421 postpartum women participated in the study. The prevalence of women who return to sexual activity six weeks after childbirth was 31.6%. The study revealed that monogamy (Adjusted Odds Ratio (AOR)= 4.4, 95% Confidence Interval (CI) (2.1, 9.4), parity (AOR= 0.11, 95% CI (0.02-0.81) and (AOR = 0.1, 95% CI (0.015-0.72), postnatal care (AOR= 1.8, 95% CI (1.01-3) and infants feeding status (AOR=2.3, 95% CI (1.3-4) were significantly associated with return of sexual activity before six weeks of childbirth. Conclusion: The findings of this study suggested that, nearly one-third of postpartum women engaged to sexual activity within six weeks of childbirth. Return of sexual activity within six weeks of childbirth associated with monogamy type of marriage, parity, postnatal care, and child feeding status. Strengthening postpartum counselling regarding the appropriate time to resume sexual activity is crucial. Regular postpartum visits following deliveries should also be encouraged by health care providers.